PRAKTIK GOVERNANCE PERBANKAN INDONESIA DITINJAU DARI ASPEK RISIKO - Harinurdin, Erwin; Setiawati, Asti; Nofiantoro, Wahyu (Jurnal Vokasi Indonesia, 2013)
Performance -based banking structures Indonesia does not have a normal life characters banking and still largely determined by the ideological and political policies of the government. Banking recovery by using a very protective manner, such as from the purchase of government bonds with limited or margin lending and guaranteed withdrawal. Various indicators such as bank loan-deposit ratio ( LDR ) and the structure of third-party funds that are still dominated by short-term funds such as checking and savings shows that the bank has not been able to carry out its primary function in the economic system, intermediation. In the framework of the restructuring and recovery of the national banking industry, Bank Indonesia has taken some of the policies that are considered necessary. Some of these policies include the implementation of the principles of risk management (according to Bassel Accor) and Know Your Customer principles. Overall, the policy is structured in parent programs are often known as the Indonesian Banking Architecture (API). API is expected to be the blue print as well as a reference for the Indonesian banking industry structure that is considered ideal for BI. Determine the number of actors performing the banking system, such as regulators, supervisors, shareholders, directors, management, internal audit, external auditors, rating agencies and owners of customer funds. The role of each differ according to the position, accountability mechanisms and social expectations. But the articulation of good governance as a protrusion of the mission, capacity and relationships to be a prerequisite for growth and stability. The method used is descriptive qualitative approach. Based on the results of the study concluded that the practice of governance in the Indonesian banking system has not been implemented optimally.